Islamic Financial Surplus for Energy and Gas Investment: Towards Financial Inclusion for Improving Living Condition of Needy and Poor in Nigeria - Amuda, Yusuff Jelili (International Journal of Energy Economics and Policy, 2023)
Undoubtedly, Nigeria is the topmost producer of energy and gas in the entire African continent. However, there is an abject poverty in the country and the global financial crisis and weaknesses of conventional financial system in predominant Muslim countries including Nigeria have not made the experts to critically explore Islamic financial surplus for energy and gas investment in order to solve the problems of needy and poor in the country. There is need to bridge the gap of financial inclusion with specific attention on energy and gas investment with specific attention on Islamic financial surplus in order to improve the living conditions of the needy and poor in the country. It is essential to utilize financial surplus derivable from energy and gas investment for sustainable financial inclusion for enhancing living condition of the needy and poor people in the society. Shari’ah compliant investment is emphatically stressed as a central climax of this study. Qualitative research design was employed in this paper using content analysis and systematic literature review. The results of the study demonstrated that Islamic financial surplus can be instrumentally related to energy and gas investment where the surplus can be adequately used for empowerment of the needy and poor people in the society. By emphasizing on Islamic financial surplus especially in connection with energy and gas investment, it will expand the understanding about Islamic economy system for financial inclusion beyond banking sector. Thus, adequate use of Islamic financial surplus in energy and gas sector will practically reduce high rate of abject poverty among the needy and the poor in the Nigerian society by attaining economic growth. Most studies on Islamic financial surplus are emphatically on banking sector. This study expands the understanding of the Islamic financial surplus by importantly relating it to energy and gas sector.